Metod of estimation of strength of composition materials with damages and cut-outs - Бородачев, Н. М.; Шевченко, О. А. (Proceedings of National Aviation University (archive), 1998)
Proposed is a new method of strength estimation of construction elements from composition materials with damages and cut-outs which is based on the strength criterion determining the condition elements of composition materials with damages and cut-outs into critical conditions. The efficiency of the method is shown on the basis of comperative analysis of the results of culculation of the plates made of laminated carbon plastic with perforations of different diameter according to the proposed method with the culculation results and traditional method and experimental data